Cognitive therapies and their impact on neuropsychiatric symptoms in mild cognitive impairment or dementia: a scoping review - Lara-Consuegra, Beatriz; Carnes-Vendrell, Anna; Torres-Hidalgo, Paula; Piñol-Ripoll, Gerard (Frontiers in Psychology, 2025)
To date, the impact of cognitive therapies on patients with dementia and mild cognitive impairment (MCI) has been studied in terms of cognition, quality of life and activities of daily living rather than in the context of neuropsychiatric symptoms (NPS). The objective of this scoping review was to collect evidence that different cognitive therapies affect the NPS of patients with MCI and dementia. A bibliographic search was conducted in the PUBMED, EMBASE, ISI WOS and SCOPUS databases through February 2025. After the elimination of duplicates, a total of 1,854 publications were identified. Among these, 42 articles were included in the analysis. These articles were reviewed by title and abstract, and then the full text was reviewed by two independent researchers with subsequent decisions about conflicts made in consultation with a third researcher. A sample of 4,089 participants was collected. All participants had undergone cognitive training interventions, cognitive rehabilitation, cognitive stimulation, art therapy, reminiscence therapy or psychobehavioural therapy and were evaluated for NPS. Depression was the most commonly analysed symptom (70% of the articles). The types of interventions that improved NPS the most were art therapy and reminiscence therapy (76 and 71% of the articles), whereas cognitive training (43%) was the least effective. While all types of therapy seemed to support the improvement of NPS, art therapy and reminiscence therapy were the most effective, especially for patients with MCI or dementia. However, studies that comprehensively evaluate the effects of cognitive therapy on NPS other than depression are lacking.